IMPLEMENTASI BIMBINGAN KELUARGA SAKINAH BAGI KETAHANAN RUMAH TANGGA DI KUA - Muh. Askar Sudana; A. Qadir Gassing; Abdul Syatar (Universitas Islam Negeri Alauddin Makassar, 2023)
AbstractThis study aims to determine how the implementation of sakinah family guidance for household resilience in KUA Maniangpajo District, Wajo Regency. The method used is descriptive qualitative in the form of field research. Data collection methods used are observation, interviews and documentation. The data analysis technique used is the Miles and Huberman model which consists of: data collection, data reduction, data presentation, and drawing conclusions/verification. The results showed that the efforts made by KUA in realizing a sakinah family for household resilience in Maniangpajo District, Wajo Regency, were through the development of religious aspects, aspects of preparing a quality generation and health aspects of prospective brides through the guidance of the sakinah family. The supporting factors in realizing a sakinah family are the rights and obligations between family members, the local government support for fostering a sakinah family, the existence of supporting facilities and infrastructure to provide counseling for sakinah family guidance for household resilience, and the community in particular and prospective brides who participate. Counselors always receive directions from the sakinah family guidance counselor for the resilience of the household. The inhibiting factor is the low understanding of Islam, understanding of creating a quality generation and understanding of health. The implications of the research are for guidance participants to understand and implement the material presented, to KUA Maniangpajo District to innovate in disseminating activities, and to the Wajo Regency government to impose sanctions on participants who do not follow the directions of the presenters.Keywords: Sakinah Family Guidance, Household Resilience.